ANALISIS KOMPARATIF METODE HIDROGRAF SATUAN SINTETIS ITB-1 DAN GAMMA-1 PADA DAS SUNGAI DELI: STUDI EMPIRIS BERBASIS DATA HISTORIS - Simanjuntak, Indi Rezki Uli (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to compare the accuracy and performance of the ITB-1 Synthetic Unit Hydrograph (HSS) and Gamma-1 Synthetic Unit Hydrograph (HSS) methods in predicting flood discharge in the Deli River Watershed (DAS), Medan, North Sumatra. Historical rainfall data from four observation stations (2007–2021) were used to calculate the design flood discharge with return periods of 2 to 100 years. Hydrological analysis was performed using the Log-Pearson Type III distribution, while hydraulic simulations used HEC-RAS 6.1. The results show that the Gamma-1 method produces a more conservative peak discharge (349,226 m³/s for a 25-year period) than ITB-1 (369,279 m³/s), with a peak time of 4.06 hours (Gamma-1) vs. 11.07 hours (ITB-1). Statistical tests show that Gamma-1 has a NSE >0.65 and a lower RMSE than ITB-1. HEC-RAS modeling confirms that the Deli River's existing capacity is only able to accommodate 10% of flood discharge, necessitating the construction of a 1–4 meter high parapet. This study recommends the use of Gamma-1 for watersheds with hydrological characteristics similar to the Deli River due to its good agreement with empirical data.